Pathological study on some common bone tumors in human - Aljeboori1, Khalil H. (Iraqi Journal of Cancer and Medical Genetics, 2017)
The study aimed to find the most common bone tumors , affected ages and to identify gross and microscopical appearances. Thirty bone tumor were obtained ; 28 cases diagnosed as primary bone tumor and 2 cases diagnosed as secondary bonetumors . The primary benign bone tumors (13) while malignant bone tumor (11) and the rest (4) cases were tumor like conditions.The primary bone tumors are diagnosed as follows osteoid osteosarcoma (4),osteoma(2),chondroblastoma(1),osteochondroma(6)chondrasarcoma (2), fibrosrcoma (1) , giant cell tumors (5) , hemangiosarcoma (1) , ewing sarcoma (1) , lymphoma (1). aneurysmal bone cysts (3) and fibrous dysplasia (1) . The secondary bone tumors (2) metastatic bronchial carcinoma case andanother case poorly differentiated prostatic carcimomaConclusion: Osteosarcoma is the most common malignant primary bone tumors and osteochondroma is the most commonbenign primay bone tumor .key word: pathology of some bone tumors in human patients